Antiplasmodial activity of faloak bark (Sterculia quadrifida, R.Br.) extract from East Nusa Tenggara, Indonesia - Tenda, Priska Ernestina; Hilaria, Maria; Ramadani, Arba Pramundita (Indonesian Journal of Pharmacology and Therapy, 2021)
The current development of antimalarial drug resistance encourages researchers to discover and develop novel antimalarials. One of its alternatives for antimalarial discovery is using medicinal plants remembering the success of artemisinin. Sterculia quardrifida R. Br. bark, locally name as faloak, is an endemic medicinal plant from East Nusa Tenggara that has been used traditionally to treat malaria. However, its antimalarial activity has not been investigated, yet. This study was aimed to evaluate the antiplasmodial activity of ethanolic extract of faloak bark against Plasmodium falciparum in vitro. Using FCR-3 P. falciparum strain, the ethanolic extract was evaluated on various concentration (1, 10, 50, and 100 μg/mL, respectively). The IC50 value was determined by the relationship between concentration and percentage of growth inhibition. The result showed that the percentage of inhibition of P. falciparum was concentration dependent, higher concentration resulting on higher percentage of inhibition with the IC50 42.399 ± 9.517 μg/mL. It can be concluded that the ethanolic extract of faloak bark have moderate antiplasmodial activity against P. falciparum in vitro.